SINR-based power schedule of sensors and DoS attackers in wireless network. (June 2022) - Xu, Guangyan; Sun, Qiuying; Liu, Hao
Abstract: In this paper, the game theory approaches are used to solve the power schedule problem in the wireless communication network. All sensors can be affected by DoS attackers when transmitting data. The game process between sensors and attackers is established as Bayesian game process. First, a Nash Equilibrium (NE) framework is proposed based on the object function consist of signal-to-interference-and-noise-ratio (SINR). Second, the total power of sensors is considered to have two types, and each type has some power levels. Unlike NE, both sensors and attackers no longer learn the specific total power of each other. However, sensors and attackers can get the type distribution of each other. In this situation, the strategies of sensors and attackers are formulated by introducing the Harsanyi transformation, and the Bayesian Nash Equilibrium (BNE) is solved. Finally, the Bayesian equilibrium strategies used by both offensive and defensive players are compared in the numerical example, which can illustrate the advantage of making full use of incomplete information. Highlights: The game theory approaches are used to solve the power schedule problem in the wireless communication network. The power strategy is considered to have different types of power levels. The Bayesian game process is established and the Bayesian Nash equilibrium of the mixed strategy is solved.